(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This article is devoted to interactive methods and their application in teaching the Russian language. Interactive methods ensure active participation of students in the language learning process and improve their communication skills. The article analyzes methods such as interactive exercises, group work, role-playing, use of technologies and games and discusses their effectiveness in the teaching process